Science and religion in India - Thomas, Renny, author.
1 online resource (224 pages).
Keywords: This book provides an in-depth ethnographic study of science and religion in the context of South Asia, giving voice to Indian scientists and shedding valuable light on their engagement with religion. Drawing on biographical, autobiographical, historical and ethnographic material, the volume focuses on scientists⁰́₉ religious life and practices, and the variety of ways in which they express it. Renny Thomas challenges the idea that science and religion in India are naturally connected and argues that the discussion has to go beyond binary models of ⁰́₈conflict⁰́₉ and ⁰́₈complementarity⁰́₉. By complicating the understanding of science and religion in India, the book engages with new ways of looking at these categories.